Peningkatan Kualitas dan Keamanan PIRT UMKM Berbasis Buah Salak di Desa Bongkok Kecamatan Paseh Kabupaten Sumedang - Eddy Yusuf; Onki Alexander (UNISBA Press, 2024)
Abstract. Salak Bongkok is a specialty of Bongkok Village, Paseh District, Sumedang Regency. MSMEs engaged in salak fruit processing have several obstacles, including inadequate processing equipment, marketing difficulties, and not understanding the flow of business legality documents. This has an impact on the quality and safety issues of